Public Opinions on Applying Adult Sex Offender Legislation to Minors Convicted of Sex Crimes. (April 2022) - Cain, Calli M.; Sample, Lisa L.
A controversial part of the Adam Walsh Act (AWA) mandates that states require minors adjudicated of certain sexual offenses to be on the sex offender registry, but not all states have complied. Our article examines how far the public in one Midwestern state that has not complied with the AWA is willing to go to manage juvenile sex offenders. We use a statewide survey of adults to examine attitudes toward applying adult sex offender penalties to minors adjudicated of a sex crime (residency restrictions, prohibitions from public schools, school zones, public parks, and social networking sites). Results indicate more than half (60%) of participants agreed that juveniles should be on the public sex offender registry. However, there was less consensus on how punitively juveniles should be treated compared with adult sex offenders. Results indicated which demographics in this state were more likely to hold punitive views toward juvenile sex offenders.